1) Marginal pdf of X:
"f_X(x)=\\int_{-\\infty}^{\\infty}f_{X, Y}(x,y)dy.\\\\\nf_{X, Y}(x,y)\\text{ --- joint pdf}.\\\\\nf_{X, Y}(x,y)=\\frac{\\partial^2}{\\partial x\\partial y}F(x,y).\\\\\nF(x,y)\\text{ --- joint CDF}.\\\\\n\\frac{\\partial}{\\partial x}F(x,y)=(1-e^{-y})e^{-x}.\\\\\n\\frac{\\partial^2}{\\partial x\\partial y}F(x,y)=e^{-(x+y)}.\\\\\nf_{X, Y}(x,y)=e^{-(x+y)} (x>0, y>0); 0 \\text{ (elsewhere)}.\\\\\nf_X(x)=\\int_{0}^{\\infty}e^{-(x+y)}dy=e^{-x}.\\\\\n\\text{So marginal pdf of X }f_X(x)=e^{-x} (x>0); 0 \\text{ (elsewhere)}.\\\\\n\\text{Marginal pdf of Y (all the computations are symmetrical)}\\\\\nf_Y(y)=e^{-y} (y>0); 0 \\text{ (elsewhere)}.\\\\\n2) X\\text{ and } Y\\text{ are independent because } f_{X,Y}(x,y)=f_X(x)f_Y(y).\\\\\nP\\{1<x<3, 1<y<2\\}=\\int_{1}^{3}\\int_{1}^{2}f_{X,Y}(x,y)dydx=\\int_{1}^{3}\\int_{1}^{2}f_{X}(x)f_{Y}(y)dydx=\\int_{1}^{3}\\int_{1}^{2}e^{-x}e^{-y}dydx=(e^{-2}-e^{-1})(e^{-3}-e^{-1})\\approx\\\\\n\\approx 0.074."
Comments
Leave a comment